2021
DOI: 10.1002/hep.32022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Phenotypic Heterogeneity of Glycogen Storage Disease Type 1a Liver Disease in Mice by Somatic CRISPR/CRISPR‐associated protein 9–Mediated Gene Editing

Abstract: BaCKgRoUND aND aIMS: Patients with glycogen storage disease type 1a (GSD-1a) primarily present with lifethreatening hypoglycemia and display severe liver disease characterized by hepatomegaly. Despite strict dietary management, long-term complications still occur, such as liver tumor development. Variations in residual glucose-6-phosphatase (G6PC1) activity likely contribute to phenotypic heterogeneity in biochemical symptoms and complications between patients. However, lack of insight into the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…We hypothesize that enhanced expression of CPT1A accompanied by the increased VLCAD and CPT2 activity in PBMC may likely represents a mechanism to counter-act malonyl-CoA-induced inhibition of hepatic CPT1 activity in response to high circulating fatty acids [ 25 ]. A possible correlation between (increased) expression of genes involved in FAO and residual G6Pase-α activity has been recently reported in G6pc −/− mice [ 33 ], supporting this hypothesis. Since 8/10 GSDIa patients carried G6PC mutations which completely abolished G6Pase-α activity [ 1 ], a correlation between FAO upregulation and estimated G6Pase-α residual activity could not be assessed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…We hypothesize that enhanced expression of CPT1A accompanied by the increased VLCAD and CPT2 activity in PBMC may likely represents a mechanism to counter-act malonyl-CoA-induced inhibition of hepatic CPT1 activity in response to high circulating fatty acids [ 25 ]. A possible correlation between (increased) expression of genes involved in FAO and residual G6Pase-α activity has been recently reported in G6pc −/− mice [ 33 ], supporting this hypothesis. Since 8/10 GSDIa patients carried G6PC mutations which completely abolished G6Pase-α activity [ 1 ], a correlation between FAO upregulation and estimated G6Pase-α residual activity could not be assessed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Demonstrated that affected mice with residual G6PC activity <60% showed a markedly increase in hepatomegaly, fasting hypoglycemia, hyperlactatemia, hypertriglyceridemia, glycogen contents, as well as oleate synthesis. These symptoms were more prominent in affected mice with G6PC activity <25% 34 …”
Section: Clinical Manifestations and Pathologic Phenotypes Of Glycoge...mentioning
confidence: 97%
“…Post-editing metabolic assays confirmed the normalized metabolic pathways in these cells, alongside their ability to maintain stable blood glucose levels under fasting conditions [ 49 ]. Rutten and colleagues generated a hepatocytic GSDIa mouse model via CRISPR-Cas9 and characterized the effects of G6PC on glucose metabolism and liver functions [ 50 ]. Their study revealed that genome-edited mouse models allow for the modeling of a variety of GSDIa phenotypes [ 50 ].…”
Section: Crispr-cas9 Gene-editing Technology For Modeling Gsdimentioning
confidence: 99%